Navigating patients with atopic dermatitis or chronic spontaneous urticaria during the COVID-19 pandemic - Haddad, Isabelle; Kozman, Kathia; Kibbi, Abdul-Ghani (Frontiers in Allergy, 2022)
A rapid spread of different strains of the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) has led to an unprecedented pandemic. Since the onset of the coronavirus disease 2019 (COVID-19) pandemic, the medical body has encountered major obstacles concerning disease management at different levels. Even though patients infected with this virus mainly present with respiratory symptoms, it has been associated with a plethora of well-documented cutaneous manifestations in the literature. However, little investigations have been conducted concerning COVID-19 and its impact on skin disorders mediated by type 2 inflammation leaving multiple dermatologists and other specialists perplexed by the lack of clinical guidelines or pathways. This review focuses on the effects of this pandemic in patients with skin disorders mediated by type 2 inflammation, specifically atopic dermatitis and chronic spontaneous urticaria. In addition, it will provide clinicians a guide on treatment and vaccination considerations for this stated set of patients.